2020
DOI: 10.1055/a-1263-1034
|View full text |Cite
|
Sign up to set email alerts
|

Acute Physiological Responses to Four Running Sessions Performed at Different Intensity Zones

Abstract: This study investigated acute responses and post 24-h recovery to four running sessions performed at different intensity zones by supine heart rate variability, countermovement jump, and a submaximal running test. A total of 24 recreationally endurance-trained male subjects performed 90 min low-intensity (LIT), 30 min moderate-intensity (MOD), 6×3 min high-intensity interval (HIIT) and 10×30 s supramaximal-intensity interval (SMIT) exercises on a treadmill. Heart rate variability decreased acutely after all se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Different types of heart rate measures are widely used in endurance training monitoring [ 26 ], and resting HRV is particularly suggested to be a useful marker when assessing recovery [ 5 ]. While acute responses in HRV are mostly related to training intensity, and sessions above the first lactate threshold delays parasympathetic reactivation compared to low-intensity sessions below the first lactate threshold [ 27 , 28 ], long-term responses to different training strategies seem to be more complicated. In the present study, no systematic changes during the training period were observed in HRV neither in INT nor in VOL.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of heart rate measures are widely used in endurance training monitoring [ 26 ], and resting HRV is particularly suggested to be a useful marker when assessing recovery [ 5 ]. While acute responses in HRV are mostly related to training intensity, and sessions above the first lactate threshold delays parasympathetic reactivation compared to low-intensity sessions below the first lactate threshold [ 27 , 28 ], long-term responses to different training strategies seem to be more complicated. In the present study, no systematic changes during the training period were observed in HRV neither in INT nor in VOL.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, examining the acute physiological response to HIIE is important as it may mediate the magnitude of changes in various outcomes when performed long-term. The majority of data concerning responses to acute HIIE was obtained from leg cycling (Olney et al, 2018), body weight exercise (Gurd et al, 2018), or treadmill running (Nuuttila et al, 2020) that mostly involve the lower extremities. However, results from these studies cannot be generalized to the upper extremity due to its lower amount of muscle mass (Sawka, 1989) and oxidative capacity (Gollnick et al, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…The timeline of HRV recovery may differ from other variables, including countermovement jump and psychological variables. Nuuttila et al [135] observed different fatigue recovery patterns for countermovement jump and post-exercise HRV depending on exercise intensity. Similarly, Vacher et al [145] noted linear changes in HRV despite nonlinear changes in perceived stress and recovery.…”
Section: Future Directionsmentioning
confidence: 99%